Polyethylene Glycol-Functionalized Siloxane Hybrid Gel Polymer Electrolytes for Lithium Ion Batteries - Lee, Albert S.; Lee, Jin Hong; Lee, Jong-Chan; Hong, Soon Man; Hwang, Seung Sang; Koo, Chong Min (AMER SCIENTIFIC PUBLISHERS, 2017)
The compatibility of diacrylate terminated polyethylene glycol-block-polydimethylsiloxane-block-polyethylene glycol was examined with an ionic liquid solution, 1 M LiTFSI in N-butyl-N-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide, and through mild UV-curing, hybrid gel polymer electrolytes were fabricated for lithium ion battery application. Obtained hybrid gel polymer electrolytes exhibited good ionic conductivity, electrochemical stability, thermal stability, and mechanical pliancy and the polyethylene glycol domains functioned to increase the ionic dissociation to improve ion conduction compared with gel polymer electrolytes fabricated with a conventional organic crosslinker. Lithium ion battery cell tests with these hybrid gel polymer electrolytes revealed that these hybrid gel polymer electrolytes hold promise as next generation electrolytes.
Keywords: IONOGELS